Pengaruh Terapi Akupresur dan Jahe Terhadap Mual Muntah pada Ibu Hamil : Systematic Literature Review - Venny Floriana; Yustina Ananti; Tri Budi Rahayu (Jurnal Indonesia Sehat, 2022)
Background: Nausea and vomiting in pregnancy is a condition of nausea and even vomiting in early pregnancy. This condition of nausea and vomiting occurs due to hormonal changes in the body, which increase dramatically in early pregnancy. Efforts that can be made to overcome nausea and vomiting in pregnancy include the provision of acupressure and ginger therapy. The purpose of this study was to determine the effect of acupressure and ginger therapy on nausea and vomiting in pregnant women with a systematic literature review. Method: This research design uses a systematic literature review, with a meta-synthetic approach. from international and national journals that meet the inclusion and exclusion criteria. From the database search results, namely PubMed, Science Direct, and Google Scholar, which are adjusted to keywords. Results: Installation of acupressure elastic bracelets for 4 days on both wrists or pressing the wrists using 3 fingers, with a duration of 5-15 minutes for 4 days can launch energy, blood flow and instruct endocrine hormones to release endorphins in the body, so that mothers feel calmer . Giving 12 ginger capsules, 2x1 for 4-7 days or 250 ml of ginger decoction, 2x1 for 4-7 days can also overcome nausea and vomiting in pregnant women because the gingerol and shogaol content in ginger is useful for blocking serotonin which functions in inducing nausea, which causes nausea. can speed up gastric emptying. The results of the journal analysis stated that acupressure and ginger therapy had an effect on nausea and vomiting in pregnant women with p-value <0.05. Conclusion: Acupressure and ginger therapy can overcome nausea and vomiting in pregnant women.